Popular Constitutionalism and Relaxing the Dead Hand: Can the People Be Trusted? - Todd E. Pettys (Washington University Law Review, 2008)
A growing number of constitutional scholars are urging the nation to rethink its commitment to judicial supremacy. Popular constitutionalists argue that the American people, not the courts, hold the ultimate authority to interpret the Constitution's many open-ended provisions whose meanings are reasonably contestable. This Article defends popular constitutionalism on two important fronts. First, using originalism as a paradigmatic example of the ways in which courts frequently draw constitutional meaning from sources deeply rooted in the past, the Article contends that defenders of judicial supremacy still have not persuasively responded to the familiar dead-hand query: Why should constitutional meanings that prevailed in the past be privileged over the meanings that a majority of Americans would assign to the Constitution's text today? The Article considers five of the leading efforts to respond to that query and argues that each of them falls short of its objective. Second, the Article responds to the most fundamental criticism that has been leveled against popular constitutionalism — namely, that the American people cannot be trusted to preserve constitutionalism's essential distinction between ordinary and fundamental law, and that citizens thus need to rely upon politically insulated judges to preserve that distinction for them. The Article identifies five reasons to believe that, if the ultimate power to interpret the Constitution's open-ended provisions were shifted from the courts to the political domain, the American people would prove themselves able and willing to distinguish between their long-term fundamental commitments and their short-term political desires in the manner that constitutionalism demands.
Keywords: Constitutionalism; Judicial supremacy; Constitutional law